2010
DOI: 10.1177/0013124510380420
|View full text |Cite
|
Sign up to set email alerts
|

Are We Supporting Teacher Success: Insights From an Alternative Route Mathematics Teacher Certification Program for Urban Public Schools

Abstract: In this article we examine induction policies and practices for new alternatively certified mathematics teachers in the country's largest urban school district, New York City. Our focus is on the support system for such teachers as it is legislated and as it is enacted. This includes the induction and general supports (e.g., mentoring, coaching, networks) that are available to mathematics teachers in the New York City Teaching Fellows Program (NYCTF). Data sources include a survey of one entire cohort of Fello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Since 2006, my colleagues and I have conducted research on the training, induction, and classroom performance of NYCTF mathematics teachers (Brantlinger & Smith, 2013; Cooley et al, 2019; Foote et al, 2011; Meagher & Brantlinger, 2011) and, hence, can speak to issues that Arenson’s article broaches. As part of a case study project, we regularly observed and interviewed nine secondary mathematics Teaching Fellows (SMTFs) in their first 2 to 3 years in the classroom.…”
Section: New York City Teaching Fellows and Mathematics Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2006, my colleagues and I have conducted research on the training, induction, and classroom performance of NYCTF mathematics teachers (Brantlinger & Smith, 2013; Cooley et al, 2019; Foote et al, 2011; Meagher & Brantlinger, 2011) and, hence, can speak to issues that Arenson’s article broaches. As part of a case study project, we regularly observed and interviewed nine secondary mathematics Teaching Fellows (SMTFs) in their first 2 to 3 years in the classroom.…”
Section: New York City Teaching Fellows and Mathematics Educationmentioning
confidence: 99%
“…Although, to become initially certified, SMTFs had to pass the mathematics content specialty test, they did not have to demonstrate their instructional competence through passing a teacher performance assessment (e.g., edTPA). Moreover, first-year mentoring provided to the typical SMTF was spotty and, in part because of this, did not clearly improve their mathematical, pedagogical, and cultural-racial competencies (Brantlinger et al, under review; Foote et al, 2011; Meagher & Brantlinger, 2011).…”
Section: New York City Teaching Fellows and Mathematics Educationmentioning
confidence: 99%
“…Research shows that novice teachers mostly face the following problems: classroom management and discipline strategies, differentiation of instruction for different groups of pupils, knowledge assessment, and the relationships with parents (Avalos & Aylwin, 2007;Fantilli & McDougall, 2009;Valenčič Zuljan et al, 2007;Menon, 2012;Demetriou et al, 2009;McCormack & Thomas, 2005;Kirby et al, 2004;Foote et al, 2011). The early period of the professional career has often been considered an administrative process of entering the educational institution and profession instead of a planned and goal-oriented process of support and professional development of novice teachers (Khamis, 2000 cited by McCormack & Thomas, 2003).…”
Section: Teachers In the Initial Period Of Their Teaching Careermentioning
confidence: 99%
“…One aspect of the national education discussion focuses on the preparation and retention of highly qualified teachers, especially in disciplines such as mathematics and science, and the acute need for effective teachers in these fields in urban areas where high poverty and poorly performing schools predominate (Alliance for Excellent Education, 2008b; Barnes, 2006;Borman & Dowling, 2008;Center for Teacher Quality, 2009;Foote et al, 2011;Lankford, Loeb, & Wyckoff, 2002;Smith & Ingersoll, 2004). For example, Bang, Kern, Luft, and Roehrig (2007) examined factors that influenced attrition rates among 115 science teachers with 1-3 years of experience in five states and found that challenging schools and classroom environments were factors that influenced the attrition of science teachers.…”
Section: Critical Shortage Areasmentioning
confidence: 99%
“…In addition, the recruitment, preparation, and retention of a high-quality teaching force for the twenty-first century in teaching fields such as bilingual education, science, special education, and mathematics continues to be a struggle for urban schools (Alliance for Excellent Education, 2008a; Center for Teacher Quality, 2009;Foote, Brantlinger, Haydar, Smith, & Gonzalez, 2011;Smith & Ingersoll, 2004). In response to the pressing need to prepare highly qualified teachers, some teacher preparation programs have responded by restructuring their curriculum to align with state and national standards, extending field experience contact hours, focusing more on diversity and social justice education, and assessing students' performance in the classroom.…”
Section: Introductionmentioning
confidence: 99%